1970
DOI: 10.22270/ajprd.v7i1.467
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Comparative Study of Different Brands of Pantoprazole Sodium Enteric Coated Tablets Marketed in Addis Ababa, Ethiopia

Abstract: Pantoprazole is a substituted benzimidazole proton pump inhibitor used in treatment of patients with serious or refractory acid-related diseases. The objective of the present study was to undertake comparative in vitro evaluation of different brands of pantoprazole sodium tablets available in different retail outlets in Addis Ababa, Ethiopia. All brands were evaluated using established procedures to assess the pharmaceutical quality characteristics. The measured thickness of studied brand tablets was found to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The uniformity in the thickness of tablets was pivotal for tablets' packaging and consumers' requirements [21]. Our findings showed that the variation of tablets' thickness was within the accepted limit; ±5%, where it was ranged between±0.01 and 0.10%.…”
Section: Discussionmentioning
confidence: 50%
“…The uniformity in the thickness of tablets was pivotal for tablets' packaging and consumers' requirements [21]. Our findings showed that the variation of tablets' thickness was within the accepted limit; ±5%, where it was ranged between±0.01 and 0.10%.…”
Section: Discussionmentioning
confidence: 50%
“…Table 3 shows the most common problems reported by these studies concerning substandard or falsified antimicrobial drugs. The determination of API content was the most examined quality control parameter most examined, being determined by all of the studies except one [41]…”
Section: Quality Control Parameters and Stated Issues Of Substandard/...mentioning
confidence: 99%
“…In this study brands NF3, NF5, NF7, and NF9 had a disintegration time of less than one minute. According to the study done by (Nigatu et al 2019), the kind, amount of excipients used in tablet formulation, and the manufacturing method, are all factors that might influence tablet disintegration time 41 . Based on this, brands NF3, NF5, and NF9 had too short disintegration time may be due to low compression force because the hardness value of those brands from those products is less than the minimum requirement of hardness value (39.23 N).…”
Section: Disintegration Time Testsmentioning
confidence: 99%